2013
DOI: 10.1016/j.psyneuen.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in methamphetamine seeking in rats: Impact of oxytocin

Abstract: Previous evidence in an animal model of drug self-administration and drug seeking showed that acute oxytocin decreased methamphetamine (meth) seeking in male rats, suggesting potential clinical efficacy for the treatment of psychostimulant addiction. However, based on the well-established role of oxytocin in reproduction and pair bond formation, it is important to know how this effect extrapolates to females. Here, we tested whether oxytocin (1 mg/kg, IP) would decrease meth seeking in female rats across vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
163
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(189 citation statements)
references
References 48 publications
21
163
5
Order By: Relevance
“…There is strong preclinical evidence for oxytocin as a treatment for psychostimulant addiction (34,35,37), and early clinical studies have confirmed that oxytocin reduces craving for marijuana and alcohol (38,39). We found that oxytocin dramatically reduced cocaine demand in animals with a standard self-administration history; this finding, in view of the relationship between demand and addiction-like behavior reported here, predicts that oxytocin may effectively treat psychostimulant dependence in the clinic.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There is strong preclinical evidence for oxytocin as a treatment for psychostimulant addiction (34,35,37), and early clinical studies have confirmed that oxytocin reduces craving for marijuana and alcohol (38,39). We found that oxytocin dramatically reduced cocaine demand in animals with a standard self-administration history; this finding, in view of the relationship between demand and addiction-like behavior reported here, predicts that oxytocin may effectively treat psychostimulant dependence in the clinic.…”
Section: Discussionsupporting
confidence: 67%
“…There is no current Food and Drug Administration-approved pharmacotherapy to evaluate the predictive validity of our economic demand procedures; however, oxytocin is a promising candidate (34,35). In preclinical testing oxytocin attenuates self-administration of psychostimulants as well as reinstatement to drug seeking (36,37), and early clinical testing confirmed that oxytocin attenuates drug craving (38,39). We tested the effect of oxytocin pretreatment on cocaine demand and reinstatement of cocaine seeking to evaluate its potential as a cocaine addiction treatment as well as to demonstrate utility of this economic approach.…”
Section: Demand Predicts Compulsive (Punished) Drug Taking Within a Mmentioning
confidence: 99%
“…Oxytocin suppressed methamphetamine-induced reinstatement in both sexes and cue-induced reinstatement in females only (Cox et al, 2013).…”
Section: Sex Differences In the Preoccupationmentioning
confidence: 91%
“…(Qi et al, 2009) as well as intra-hippocampal and intra-medial prefrontal cortex (Han et al, 2014) administration of OT prevented stress-induced reinstatement of METH-seeking. Similarly, intra-AcbC , as well as peripheral (Carson et al, 2010;Cox et al, 2013) administration of OT attenuated METH-primed reinstatement in rodents. In addition, Hicks et al (2014) showed that a 10-day oxytocin administration during adolescence was able to decrease the motivation to self-administer METH and to attenuate priming-induced reinstatement of METH-seeking during adulthood in rats.…”
Section: Introductionmentioning
confidence: 86%